Subtle Intricacies Identified during Streptozotocin-Induced Diabetes in Wistar Rats - Brahmam, Bheemisetty; Begum, Farmiza; Yarlagadda, Dani Lakshman; Shenoy, Rekha Raghuveer; Lewis, Shaila Angela (Indian Journal of Pharmaceutical Education and Research, 2023)
Aim: This study aimed to establish the dose of streptozotocin required to induce Type -1 diabetes in Wistar rats. Background: Streptozotocin is currently employed worldwide to induce insulin-dependent diabetes mellitus also known as Type 1 diabetes mellitus in experimental animals. Though many reports on the use of streptozotocin induction of diabetes are reported in the literature, they were not reproducible. Moreover, there was no mention of the mortality associated with the same as well as the conditions followed during the study. Materials and Methods: In the present study, the dose, route, and solvent used for streptozotocin were investigated. Various doses of streptozotocin 55, 50, 40, and 35mg/kg dissolved in either freshly prepared cold 10mM sodium citrate buffer (pH 4.5) or normal saline solution was administered intraperitoneally as well as intravenously. For intraperitoneal administration, the dose-volume was 10mL/kg whereas for intravenous administration the dose-volume was 2mL/Kg. Different routes were employed to ascertain the cause of mortality for which an autopsy was performed. Besides mortality rate was also determined. Results and Discussion: The findings of the study revealed that a 35-40mg/kg dose of streptozotocin showed less percentage mortality and successful induction of diabetes. Conclusion: Mortality (10-20%) was observed at a dose of 35-40mg/kg streptozotocin. Therefore, streptozotocin (35-40mg/kg) was confirmed to be safe and effective for the induction of diabetes in Wistar rats. This paper highlights subtle intricacies observed during induction of diabetes in Wistar rats using streptozotocin
Keywords: Male Wistar rats; Streptozotocin; Type-1 diabetes; 5% dextrose; Mortality; Normal saline solution